The Productivity and Nutrient Use Efficiency of Rice–Rice–Black Gram Cropping Sequence Are Influenced by Location Specific Nutrient Management - Shankar, Tanmoy; Banerjee, Mahua; Malik, Ganesh Chandra; Dutta, Sudarshan; Maiti, Debtanu; Maitra, Sagar; Alharby, Hesham; Bamagoos, Atif; Hossain, Akbar; Ismail, Ismail A.; EL Sabagh, Ayman (Sustainability, 2021)
Nutrient management is critical for rice farming because the crop is grown under diverse conditions, and in most cases, the existing nutrient management practices fail to achieve an attainable yield target. During recent years site specific nutrient management gained importance for a target yield with maximum nutrient use efficiency. Sufficient research work has not been carried out in this direction so far in the rice–rice–pulse (black gram) sequential cropping system under the red and lateritic belt of West Bengal, India. A multi-locational field experiment was conducted from July 2013 to June 2015 at three different locations, namely, Guskara (Burdwan district) and Benuriya (Birbhum district) villages in farmers’ fields and at the university farm of Visva-Bharati, Sriniketan, West Bengal, India. The performance of nutrients was tested by providing ample doses of N, P, K, S, and Zn compared to the omission of these nutrients. The growth parameters, such as crop biomass production, leaf area index, and number of tillers, and yield attributes and yield were influenced by nutrient management treatments. Application of 100% of N, P, K, S, and Zn resulted in its superiority to other nutrient management options studied, and a similar trend was also noted with the treatment in the expression of nutrient use efficiency (NUE) and nutrient response (NR). The available N, P, K, S, and Zn contents in soil increased steadily due to the increase in fertilizer application. The study concluded that optimization of NPK in the rice–rice–pulse cropping system on target yield along with need-based S and Zn application was beneficial for higher productivity.